2002
DOI: 10.1111/1467-9280.00475
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Load Interference in Syntactic Processing

Abstract: Participants remembered a short set of words while reading syntactically complex sentences (object-extracted clefts) and syntactically simpler sentences (subject-extracted clefts) in a memory-load study. The study also manipulated whether the words in the set and the words in the sentence were of matched or unmatched types (common nouns vs. proper names). Performance in sentence comprehension was worse for complex sentences than for simpler sentences, and this effect was greater when the type of words in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
188
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(213 citation statements)
references
References 20 publications
19
188
3
3
Order By: Relevance
“…9, page 4 of 25 with adults (Mak, Vonk & Schriefers 2002;Traxler et al 2005;Lowder & Gordon 2014). In studies with adults, Gordon and colleagues (Gordon, Hendrick & Johnson 2001;Gordon, Hendrick & Levine 2002) found an advantage with the mismatch of a lexical-NP restriction. According to Gordon et al, there is a memory load in ORCs with matching feature sets: in both adults and children, the greater the difference between the feature sets of the target and the intervener, the weaker the interference effects in the comprehension of ORCs.…”
Section: Introductionmentioning
confidence: 99%
“…9, page 4 of 25 with adults (Mak, Vonk & Schriefers 2002;Traxler et al 2005;Lowder & Gordon 2014). In studies with adults, Gordon and colleagues (Gordon, Hendrick & Johnson 2001;Gordon, Hendrick & Levine 2002) found an advantage with the mismatch of a lexical-NP restriction. According to Gordon et al, there is a memory load in ORCs with matching feature sets: in both adults and children, the greater the difference between the feature sets of the target and the intervener, the weaker the interference effects in the comprehension of ORCs.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that comprehension of object relatives deteriorated sharply when similarity increased, resulting in a structure (subject versus object relative) by similarity interaction. Self-paced reading tasks have also identified stronger similarity/interference effects in non-canonical sentences, leading to longer latencies in the region of the second NP (Gordon et al 2001(Gordon et al , 2002(Gordon et al , 2004. There is also clear evidence that avoidance in production is strongly influenced by interference.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gordon et al (2002) found that interference effects are greater for non-canonical sentences. The study involved processing subject and objective relatives while remembering a list of nouns, which were either similar or dissimilar to the NPs in the sentences (dancer-fireman versus Joey-fireman).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers, on the other hand, have claimed for shared resources, where verbally mediated tasks call for the same pool of verbal WM resources irrespective of whether the stimuli tap syntactic processing or not (e.g., King and Just, 1991;Just and Carpenter, 1992). Both theories have found some support in subsequent studies (Gordon et al, 2002;Fedorenko et al, 2006). The mental architecture of verbal WM is nevertheless an important issue here, because the shared resources hypothesis would predict broader potential transfer effects after verbal WM training than the dedicated resource hypothesis.…”
mentioning
confidence: 96%